The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/bjs.1800811136
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of whole-body positron emission tomography with [18F]fluorodeoxyglucose in recurrent colorectal cancer

Abstract: To assess the clinical value of whole-body positron emission tomography (PET) with [18F]fluorodeoxyglucose (FDG) in recurrent colorectal cancer, 35 patients were studied: 15 had resectable liver metastases, one a resectable lung metastasis, eight resectable pelvic recurrence, eight a presacral mass with equivocal findings on imaging, and three increasing serum levels of carcinoembryonic antigen (CEA) without clinical or radiological signs of recurrent disease. PET affected management decisions in seven of 16 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(59 citation statements)
references
References 16 publications
2
52
0
5
Order By: Relevance
“…In most patients with NSGCT mature teratoma was found in the residual mass (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In five of them (16)(17)(18)(19)(20) FDG uptake was found (SUV 1.7-3.7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most patients with NSGCT mature teratoma was found in the residual mass (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In five of them (16)(17)(18)(19)(20) FDG uptake was found (SUV 1.7-3.7).…”
Section: Resultsmentioning
confidence: 99%
“…In five of them (16)(17)(18)(19)(20) FDG uptake was found (SUV 1.7-3.7). On visual analysis, only patients 16 and 17 had a suspect lesion at PET.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpected extrahepatic metastases were detected in 14 locations in ten patients. In a previous study on 35 patients, Beets et al from the same group, evaluated the clinical impact of PET on management [148]. Sixteen patients presented with "resectable" metastases, eight with resectable pelvic recurrences, eight with a presacral mass of uncertain nature and three with an isolated increase in the carcinoembryonic antigen (CEA) level.…”
Section: Staging Of Patients With Suspected or Demonstrated Recurrencesmentioning
confidence: 99%
“…Whole-body position emission tomography, using fluoro-deoxyglucose (FDG-PET) with 18 F as the position emitting isotope, has a sensitivity as high as 92% to 100%, with a specificity of 85% to 100%. [22][23][24][25][26][27] Schiepers et al 25 reported a 93% sensitivity with FDG-PET compared with 60% with CT. Radioimmunodetection with monoclonal antibodies may also be useful in select cases. In some reports, indium 111 CYT-103 (OncoScint, Cytogen, Princeton, NJ) appeared to be more sensitive than CT in detecting lesions outside the liver.…”
Section: Evaluation Of the Patient With Hepatic Metastasesmentioning
confidence: 99%